A needs analysis of mobile game-based learning media for visual communication design in Padang vocational schools - Yuliawati Yunus; Popi Radyuli (Jurnal Pendidikan Vokasi, 2025)
This study aims to analyze the need for mobile game-based learning media (MGBLM) in visual communication design (VCD) subject in vocational high schools. This study employs a quantitative descriptive approach using a survey technique involving two groups of respondents: 12 VCD teachers and 255 students from 12 public and private vocational high schools in Padang city during the odd semester of the 2024/2025 academic year. Data were collected through a likert-scale questionnaire and analyzed descriptively using percentages. The results of the study indicate a high level of need, with 96% of teachers and 94% of students indicating very needed for the integration of MGBLM in the VCD learning process. The study also found that teachers fully agree that mobile-based learning media should align with curriculum objectives and support student engagement through interactive visual learning. Similarly, more than 90% of students agreed or strongly agreed that they needed mobile game-based learning media that suited their learning styles and supported independent and enjoyable VCD learning. These findings emphasize the importance of developing mobile game-based learning media tailored to the needs of vocational high school students, especially in creative subject such as visual communication design. These results serve as a foundation for further development of educational media using structured models such as Hanafin and Peck. This study is unique because it specifically maps the needs for mobile game-based learning in VCD subject, an area rarely explored in Indonesian vocational schools.